Case Report: Genomic characterization of a rare skull-base plasmacytoma - Alanya, Hasan; Kasturi, Sreekar; Yalcin, Kanat; Gultekin, Batur; Kumar, Deepika; Samuel, Natalia; Figuera, Diego Samper; Mishra-Gorur, Ketu; Gunel, Murat; Erson-Omay, E. Zeynep; Omay, S. Bulent (Frontiers in Oncology, 2025)
Skull-base plasmacytoma (SBP) is a rare plasma cell neoplasm that typically presents as a slow-growing skull-base lesion in older adults; however, its molecular underpinnings are poorly characterized, limiting targeted therapeutic interventions and precise prognostication. We describe the case of a 67-year-old female who presented with progressive headaches, whose imaging and biopsy confirmed a solitary SBP with no evidence of systemic disease. Whole-exome sequencing revealed an elevated somatic copy number alteration burden and pathogenic variants in ARID1A, KMT2D, BCL7A, PTPN11, and NUP214, suggesting disruptions in chromatin remodeling, B-cell neoplasm pathogenesis, and oncogenic signaling driving the tumorigenesis. These findings provide novel insights into molecular landscape of SBP, highlighting potential for risk stratification and targeted therapy development. The case underscores the importance of comprehensive genomic profiling in rare skull-based tumors to enhance our understanding of their biology and to guide personalized clinical management.